2018
DOI: 10.5194/acp-2018-1085
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating the Recent 2+26 Regional Strategy for Air Quality Improvement During Two Orange Air Pollution Alerts in Beijing: variations of PM<sub>2.5</sub> concentrations, source apportionment, and the relative contribution of local emission and regional transport

Abstract: <p><strong>Abstract.</strong> To comprehensively evaluate the effects of the recent <q>2+26</q> regional strategy for air quality improvement, we compared the variations in PM<sub>2.5</sub> concentrations in Beijing during four pollution episodes with different emission-reduction strategies. The <q>2+26</q> strategy implemented in March 2018 led to a mean PM<sub>2.5&lt… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In contract, the contributions of sulfate to PM 1 were 12% both in BJ and XL, which were obviously lower than that in nitrate. Recent studies have indicated the increasing role of nitrate in winter haze pollution in BJ (Chen et al, 2018;Li et al, 2019;W. Xu et al, 2019).…”
Section: Mass Concentrations and Chemical Compositionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contract, the contributions of sulfate to PM 1 were 12% both in BJ and XL, which were obviously lower than that in nitrate. Recent studies have indicated the increasing role of nitrate in winter haze pollution in BJ (Chen et al, 2018;Li et al, 2019;W. Xu et al, 2019).…”
Section: Mass Concentrations and Chemical Compositionsmentioning
confidence: 99%
“…Numerous studies have been performed using AMS, and a variety of views have been proposed Hu et al, 2016;Huang et al, 2018;Li et al, 2018;Sun et al, 2014;Sun et al, 2016). The chemical compositions and sources in different cities of the NCP are quite different (Chen et al, 2018;Ge et al, 2017;Huang et al, 2018;Li et al, 2017;Li et al, 2018). For example, nitrate was the dominant inorganic component in Beijing in recent years (Chen et al, 2018;Ge et al, 2017); however, in industrialized cities southwest of Beijing, sulfate and primary emissions dominated by coal and biomass combustion account for a large proportion of fine particulate matter (Huang et al, 2018;Li et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this approach does not capture the interactions between secondary PM precursor species which may be particularly important during episodes with high nitrate levels (Burr and Zhang, 2011). Recently, Chen et al (2019) used the PSAT approach at 12 km resolution to calculate source contributions from districts included in the Chinese government's "2+26" regional emission control strategy, although they did not include the effect of surrounding regions in their analysis, which may be needed to formulate successful emission control policy under less favourable meteorological conditions. Moreover, none of these studies provide information on the temporal contribution of different sources which is important for the design of short-term emergency control measures.…”
mentioning
confidence: 99%
“…programme (Chen et al, 2019). While we have focused on the October-November 2014 period associated with the important APEC Summit to explore source sensitivities, we note that emissions are changing rapidly in both Beijing and surrounding regions (Cheng et al, 2019;Zheng et al, 2018) leading to spatial and temporal changes in air pollution (Xiao et al, 2020;Xu and Zhang, 2020).…”
mentioning
confidence: 99%